Enhancing competitiveness: Driving and facilitating factors for industry 4.0 adoption in Thai manufacturing - Nuchjarin Intalar; Yasushi Ueki; Chawalit Jeenanunta (Economies, 2024)
Adopting Industry 4.0 (I4.0) is inevitable for Thailand's manufacturing sector to remain competitive because global markets increasingly demand higher quality, faster delivery, and greater customization. While firms need to enhance productivity and optimize resource utilization, they also need to reduce operation costs, which require advanced technologies and data-driven operations. However, successful adoption requires skilled human resources, which is challenging for small and medium-sized enterprises (SMEs). This research explores factors driving and facilitating the implementation of Industry 4.0 (I4.0) in Thai manufacturing firms among SMEs and large firms. We employed qualitative analysis using semi-structured interviews with SMEs and large manufacturing firms in Thailand. Five key factors emerged as crucial for I4.0 adoption: awareness of I4.0, strong and proactive support from top management, self-funding capabilities, and effective human resource development strategies. While large multinational enterprises (MNEs) possess more significant resources and capabilities to adopt I4.0 technologies, SMEs face considerable challenges. They require a strategic approach tailored to their unique needs and resources to develop a feasible I4.0 roadmap. Additionally, governments and industry associations can play a significant role by providing training, funding, and other resources to empower SMEs to embrace I4.0.
Keywords: 330; capability building; digital transformation; human resource development strategy; Industry 4.0; top management support